Metoprolol, N-Acetylcysteine, and Escitalopram Prevents Chronic Unpredictable Mild Stress-Induced Depression by Inhibition of Endoplasmic Reticulum Stress - Yang, Lixia; Zheng, Lei; Wan, Yan; Chen, Zhenghong; Li, Peifan; Wang, Yiming (Frontiers in Psychiatry, 2018)
Background: Endoplasmic reticulum stress (ERS) has been recently suggested to be activated in the major depressive disorder (MDD). However, whether ERS is a potential therapeutic target for MDD is largely unknown. Here we attempted to assess the preventive effect of metoprolol (MET), N-acetylcysteine (NAC), and escitalopram (ESC) on chronic unpredictable mild stress (CUMS)-induced depression and investigate whether ERS mediates the antidepressant role of these drugs. Method: Forty-five sprague-dawley rats were randomly divided into five groups: control, CUMS, CUMS+ESC, CUMS+NAC, and CUMS+MET. Weight measurement, open field activity and sucrose preference were performed before and after stress. Hippocampal nerve cells and capillary ultrastructure were observed by transmission electron microscope, and hippocampal cells apoptosis were detected by flow cytometry. Furthermore, expression of ERS markers glucose-regulated protein 78 (GRP78), C/EBP-homologous protein (CHOP), and caspase-12 were measured by western blot and qRT-PCR. Results: The CUMS-induced rats showed significantly increased depressive-like behaviors including decreased open field activity and sucrose preference. Moreover, CUMS-exposed rats exhibited significantly increased hippocampal cell apoptosis, and showed damage in hippocampal nerve cells and capillary ultrastructure. Furthermore, ESC and NAC not only mitigated depressive-like behaviors, but also decreased apoptosis and pathologies, while MET fail to decrease apoptosis. Moreover, CUMS stimulation significantly elevated ERS by increasing the levels of GRP78, CHOP, and decreasing the level of caspase-12, while ESC, NAC, and MET significantly decreased the ERS. Conclusion: ESC, NAC, and MET might prevent the MDD partly through inactivating the ERS. These findings demonstrated ERS as a novel treatment target for depression.